2020
DOI: 10.3390/v12101177
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Zika Virus xrRNA1-Dependent sfRNA1 Production Results in Tissue-Specific Attenuated Viral Replication

Abstract: The Zika virus (ZIKV), like other flaviviruses, produces several species of sub-genomic RNAs (sfRNAs) during infection, corresponding to noncoding RNA fragments of different lengths that result from the exonuclease degradation of the viral 3′ untranslated region (UTR). Over the course of infection, these sfRNAs accumulate in the cell as a result of an incomplete viral genome degradation of the 3′ UTR by the host 5′ to 3′ exoribonuclease, Xrn1. The halting of Xrn1 in the 3′ UTR is due to two RNA pseudoknot stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
(158 reference statements)
1
10
0
Order By: Relevance
“…However, as this deletion causes major structural disruption in viral 3′UTR, which is also required for viral replication ( 40 ), this model does not allow separation of the effects caused by sfRNA deficiency from the effect of compromised genome integrity. Another study used partially sfRNA-deficient ZIKV (still producing sfRNA2, equivalent to our xrRNA1′ mutant) and found that the mutation did not affect viral replication in cell lines while causing reduced maternal blood viremia and placental viral loads in a mouse pregnancy model ( 41 ). However, this study could not assess the effect of sfRNA on transplacental virus dissemination and fetal brain infection, as even WT ZIKV in these experiments was not detected in fetal heads ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as this deletion causes major structural disruption in viral 3′UTR, which is also required for viral replication ( 40 ), this model does not allow separation of the effects caused by sfRNA deficiency from the effect of compromised genome integrity. Another study used partially sfRNA-deficient ZIKV (still producing sfRNA2, equivalent to our xrRNA1′ mutant) and found that the mutation did not affect viral replication in cell lines while causing reduced maternal blood viremia and placental viral loads in a mouse pregnancy model ( 41 ). However, this study could not assess the effect of sfRNA on transplacental virus dissemination and fetal brain infection, as even WT ZIKV in these experiments was not detected in fetal heads ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study used partially sfRNA-deficient ZIKV (still producing sfRNA2, equivalent to our xrRNA1′ mutant) and found that the mutation did not affect viral replication in cell lines while causing reduced maternal blood viremia and placental viral loads in a mouse pregnancy model ( 41 ). However, this study could not assess the effect of sfRNA on transplacental virus dissemination and fetal brain infection, as even WT ZIKV in these experiments was not detected in fetal heads ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent results demonstrated that sfRNA acts as one of the viral factors of ZIKV pathogenesis in the developing brain [ 17 ]. Production of sfRNA was also shown to be a requirement for trans-placental dissemination of the virus and infection of the fetal brain in the mouse pregnancy model [ 17 , 25 ]. In addition, in human brain organoids and cultured neural progenitors, WT virus-producing sfRNA induced the apoptosis of infected cells, while viruses deficient in sfRNA production were much less potent in inducing apoptosis and were unable to cause the death of the infected brain organoids [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nomenclature referred by Liu et al., 2018 for the stem loops present in the variable region are in parenthesis. The variable regions of West Nile (WNV- Tilgner et al., 2005 ; Funk et al., 2010 ; Clarke et al., 2015 , and Göertz et al., 2016 ), Japanese encephalitis (JEV- Chen et al., 2018 and Xing et al., 2021 ), Tick borne encephalitis (TBEV- Muto et al., 2018 and Sakai et al., 2015 ) and Zika viruses (ZIKV- Schneider and Wolfinger, 2019 , and Sparks et al., 2020 ) are shown. Additionally, the first dumbbell structure of ZIKV ( Schneider and Wolfinger, 2019 ) is also included.…”
Section: Flavivirus 3’ Utrmentioning
confidence: 99%
“…In some TBE viruses, there are seven stem–loops: SL1-SL7 ( Sakai et al., 2015 ; Ochsenreiter et al., 2019 ). These SL structures are conserved among flaviviruses and are responsible for the inhibition of the activity of Xrn-1 nuclease, an important process for the generation of sfRNAs, which participate in the antiviral evasion mechanisms in both mammals and mosquitoes ( Funk et al., 2010 ; Villordo et al., 2015 ; Göertz et al., 2016 ; Chen et al., 2018 ; Bellone et al., 2020 ), including viral adaptation, fitness, virulence, and tissue tropism ( Funk et al., 2010 ; Liu et al., 2018 ; Finol and Ooi, 2019 ; Sparks et al., 2020 ). In WNV, the SL-III has an inhibitory effect on translation since its deletion increase viral translation efficiency ( Berzal-Herranz et al., 2022 ).…”
Section: Flavivirus 3’ Utrmentioning
confidence: 99%